2017
DOI: 10.1021/acs.biochem.7b00971
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biosynthesis of 1-Mercaptoethanesulfonic Acid (1-MES), an Analogue of Coenzyme M, Found Widely in the Methanogenic Archaea

Abstract: Here I report on the identification of 1-mercaptoethanesulfonic acid (1-MES), an analogue of 2-mercaptoethanesulfonic acid (coenzyme M, HSCoM). 1-MES and HSCoM were both present in the growth media of eight different methanogens at concentrations ranging from ∼1 to 100 μM. In an effort to determine a chemical origin of 1-MES, several plausible chemical routes were examined each assuming that HSCoM was the precursor. In all examined routes, no 1-MES was formed. However, 1-MES was formed when a solution of vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Acetate grown M. barkeri cells were supplied by D. Grahame and stored at −80°C. The other organisms described in Table 1 were supplied by S. Shima (Max Planck Institute for Terrestrial Microbiology, Marburg, Germany), grown as previously reported ( 78 ), and stored as frozen cell pellets at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Acetate grown M. barkeri cells were supplied by D. Grahame and stored at −80°C. The other organisms described in Table 1 were supplied by S. Shima (Max Planck Institute for Terrestrial Microbiology, Marburg, Germany), grown as previously reported ( 78 ), and stored as frozen cell pellets at −80°C.…”
Section: Methodsmentioning
confidence: 99%